Distribution of technetium-99m PEG-liposomes during oligofructose-induced laminitis development in horses. Issue 2 (November 2015) - Underwood, Claire; Pollitt, Christopher C.; Metselaar, Josbert M.; Laverman, Peter; van Bloois, Louis; van den Hoven, Jolanda M.; Storm, Gert; van Eps, Andrew W.
Highlights: This study investigated whether polyethylene-glycol liposomes accumulate in the lamellar tissue during laminitis development. 99m Tc-PEG-liposomes were administered to normal horses and horses with oligofructose-induced laminitis. Scintigraphy and lamellar tissue collection demonstrated liposome accumulation in the lamellar tissue of horses with laminitis. Liposomes may have potential for targeted lamellar drug delivery in acute laminitis. Abstract: Liposomes are phospholipid nanoparticles used for targeted drug delivery. This study aimed to determine whether intravenous liposomes accumulate in lamellar tissue during laminitis development in horses so as to assess their potential for targeted lamellar drug delivery. Polyethylene-glycol (PEG) coated liposomes were prepared according to the film hydration method and labelled using 99m Tc-hexamethyl-propylene-amine-oxime. Six horses received 10 g/kg oligofructose via nasogastric tube to induce laminitis, and four control horses received water via nasogastric tube. All horses received 300 µmol 99m Tc-PEG-liposomes (5.5 GBq) plus 5.5 µmol/kg PEG-liposomes by slow intravenous infusion. Scintigraphic imaging was performed at 0, 6 and 12 h post-infusion. Technetium-99m liposome uptake was measured in regions of interest over the hoof, fetlock and metacarpus. At the study end-point horses were euthanased, tissue samples collected and tissue liposome levels were calculated as the percentage of the injected dose of 99m Tc-liposomes per kilogram of tissue. Data were analysed non-parametrically. All horses receiving oligofructose developed clinical and histological signs of laminitis. Technetium-99m liposome uptake in the hoof increased with time in laminitis horses ( P = 0.04), but decreased with time in control horses ( P = 0.01). Technetium-99m liposome levels in lamellar tissue from laminitis horses were 3.2-fold higher than controls ( P = 0.02) and were also higher in laminitis vs. control skin, muscle, jejunum, colon, and kidney ( P < 0.05). Liposomes accumulated in lamellar tissue during oligofructose-induced laminitis development and demonstrated potential for targeted lamellar drug delivery in acute laminitis. This study provides further evidence that lamellar inflammation occurs during laminitis development. Liposome accumulation also occurred in the skin, muscle, jejunum, colon and kidneys, suggesting systemic inflammation in this model.